The Effectiveness Of Classroom Discussion In Improving English Speaking Skill Among The Students Of SMP N 3 Depok - Setyawan, Agustinus Hary (LPPM Universitas Mercu Buana Yogyakarta, 2015)
The objective of the research is to investigate whether or not there is a significant difference in the mastery of the speaking skill between the students who are taught by using classroom discussion and those who are taught without using classroom discussion. This study is a quasi-experimental study employing two groups. The experimental group is 8A and the control group is 8C. The data were collected by using an achievement test. The data of both pre-test and post-test scores from the control and experimental groups were analyzed by using inferential statistics. To test the hypothesis, the researcher used t-test to find out the differences of speaking skill mastery achievement between control and experimental groups. The result of post-test indicates that t o is higher than the t value at the significance level of 5%, i.e. 2.106<2.000. The level significance is 0.037. It is lower than 0.05. It was found that the mean of the post-test scores and gained scores of the experimental group were higher than that of the control group. The standard deviation of the experimental group decreases from 7.30 to 6.92 or the scores of the experimental group from pre-test to post-test are more homogenous. While, the standard deviation of the control group increases from 7.53 to 8.36 or the scores of the control group from pre-test to post-test are more heterogeneous. Besides, the mean of experimental group increases 207% from the standard deviation of the pre-test. While the mean of the control group also increases 147% from the standard deviation of the pre-test. It is found that classroom discussion is effective in improving English learning achievement in student’s mastery of speaking and there is a significant difference in between the both class.